2015
DOI: 10.1016/j.scitotenv.2014.10.084
|View full text |Cite
|
Sign up to set email alerts
|

Environmental health impacts of unconventional natural gas development: A review of the current strength of evidence

Abstract: Rapid global expansion of unconventional natural gas development (UNGD) raises environmental health concerns. Many studies present information on these concerns, yet the strength of epidemiological evidence remains tenuous. This paper is a review of the strength of evidence in scientific reporting of environmental hazards from UNGD activities associated with adverse human health outcomes. Studies were drawn from peer-reviewed and grey literature following a systematic search. Five databases were searched for s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
137
0
4

Year Published

2016
2016
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 186 publications
(142 citation statements)
references
References 80 publications
1
137
0
4
Order By: Relevance
“…They found "many chemicals used during the fracturing and drilling stages of gas operations may have long-term health effects that are not immediately expressed". On the topic of further research, Werner et al [64] stated that the literature does not allow for any negative health impacts associated with hydraulic fracturing to be ruled out. McKenzie et al [65] and McKenzie et al [66] suggested that the impact of atmospheric emissions on human health warrant further study, emphasizing that they potentially have non-trivial effects on maternal health.…”
Section: F Castro-alvarez Et Al Renewable and Sustainable Energy Rementioning
confidence: 99%
“…They found "many chemicals used during the fracturing and drilling stages of gas operations may have long-term health effects that are not immediately expressed". On the topic of further research, Werner et al [64] stated that the literature does not allow for any negative health impacts associated with hydraulic fracturing to be ruled out. McKenzie et al [65] and McKenzie et al [66] suggested that the impact of atmospheric emissions on human health warrant further study, emphasizing that they potentially have non-trivial effects on maternal health.…”
Section: F Castro-alvarez Et Al Renewable and Sustainable Energy Rementioning
confidence: 99%
“…The groups also enumerated problems with the mitigation efforts, explaining that the "DOGGR cannot assure that the limited set of mitigation measures it mentions will be enforceable, even at sites where it will serve as Lead Agency, because it has not clearly specified which measures it intends to enforce." [69] Additionally, although there is evidence of significant [70] impacts to health [71][72][73], no separate public health study was conducted [14].…”
Section: California's Environmental Impact Reports and Feedbackmentioning
confidence: 99%
“…While these findings suggest that fracking activity may lead to adverse health outcomes, the evidence for a strong causal link between fracking and health is quite limited (Mitka (2012), Werner et al (2015)). However, even if there is not a substantially elevated direct health risk, the industrial activity involved in creating a well could generate additional trucking volume with its own health risks (Mathews (2015), Graham et al (2015)).…”
Section: Environmental Risksmentioning
confidence: 99%